Beyond rules and resources: Parliamentary scrutiny of EU policy proposals. (December 2015) - Finke, Daniel; Herbel, Annika
This article examines the factors that shape parties' motivation to invest time and other resources in scrutinizing European Union policy proposals. We distinguish between two different motivations to engage in scrutiny activities. First, parties use such mechanisms to influence the national position directly. Second, parties play a two-level game and use scrutiny to manipulate their negotiator's domestic constraints. Both arguments depend on a set of conditions, namely the government's relative strength in Brussels, the transparency of the European Union decision-making process as well as the government's relative strength and cohesion in the domestic arena. On the empirical side, we study scrutiny at the level of committees in the national parliaments of Finland, France, Germany, Ireland, Italy, Poland, Slovakia, and the United Kingdom over a 13-year period, during which 32 governments are covered. Our findings suggest that parties deploy scrutiny to shift the domestic constraint strategically, but only if such a shift can be communicated convincingly to the international bargaining partners. Moreover, our findings suggest that opposition parties employ such measures to influence the position of a weak government.